1997
DOI: 10.1002/art.1780401113
|View full text |Cite
|
Sign up to set email alerts
|

Localization of hepatitis C virus in cutaneous vasculitic lesions in patients with type II cryoglobulinemia

Abstract: Objective. To investigate the role of hepatitis C virus (HCV) in the pathogenesis of the cutaneous vasculitis in patients with type I1 cryoglobulinemia.Methods. Using in situ hybridization detection of HCV, we studied 6 test patients and various control subjects. Serum HCV was quantitated, cryoglobulins were analyzed by column chromatography at 37"C, and lowdensity lipoprotein (LDL) receptors on keratinocytes were detected using LDL labeled with fluorescent dye.Results. In the cutaneous vasculitic lesions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 21 publications
(9 reference statements)
4
51
1
6
Order By: Relevance
“…41 Again, however, contradictory data have been reported: immunohistochemistry has failed to stain non-structural HCV proteins in the skin of cryoglobulinemic, chronic hepatitis C patients, 42 and a careful RT-PCR study has suggested the absence of HCV RNA in salivary gland epithelial cells. 43 Finally, the presence of HCV in the brain has only been anecdotally reported 44 and awaits confirmation.…”
mentioning
confidence: 99%
“…41 Again, however, contradictory data have been reported: immunohistochemistry has failed to stain non-structural HCV proteins in the skin of cryoglobulinemic, chronic hepatitis C patients, 42 and a careful RT-PCR study has suggested the absence of HCV RNA in salivary gland epithelial cells. 43 Finally, the presence of HCV in the brain has only been anecdotally reported 44 and awaits confirmation.…”
mentioning
confidence: 99%
“…15 Furthermore, it has been demonstrated that low-density lipoprotein re- ceptors are upregulated on keratinocytes in cutaneous vasculitis lesions of HCV-infected patients compared with normal skin. 22 A higher proinflammatory cytokine production (i.e., tumor necrosis factor ␣) has been observed in the peripheral blood and liver of HCV-cryoglobulinemic patients compared with their cryoglobulin-negative couterparts. 23,24 Hence, upregulation of low-density lipoprotein receptors associated with inflammation may result in lipid accumulation in the liver of HCV-cryoglobulinemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the endocytosis of viral particles is associated with LDLR activity, based upon the correlation of cells positive for HCV and for LDLR. 38 Furthermore, continued stimulation of LDLR expression enhanced virus replication in vitro. 39 The serum concentration of beta-lipoproteins is thought to influence HCV concentration, as the former could inhibit the binding of the virus to its proposed receptor, the LDLR.…”
Section: Discussionmentioning
confidence: 99%